2018
DOI: 10.1002/cjce.23237
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microwave‐assisted extraction parameters and characterization of phenolic compounds in Yellow European Plums

Abstract: Yellow European Plums (YEPs) are a rich source of phenolic compounds and antioxidants, which can be obtained using microwave‐assisted extraction (MAE). During this study, two MAE experiments were performed to optimize MAE extraction parameters and the MAE process using YEPs. The first experiment was to determine the influence of independent variables such as solvent concentration (20, 60, and 100 %) and solid‐to‐solvent ratio (0.05, 0.1, and 0.15 g/mL), on the yield of total phenolic content (TPC) and antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The responses of TPC and AC of the chestnut peel extracts are shown in Table 2. The lowest values were obtained with pure ethanol and methanol, which is in agreement with previous studies (Ashraf et al, 2016;Riciputi et al, 2018;DiNardo et al, 2019;Lasano et al, 2019). Results showed that the highest value of TPC (41.92 mg GAE/g DM) was achieved with ethanol, which is in concordance with the result of Stevigny et al (2007), while the highest value of AC (42015.95 mmol AAE/100 g DM) was obtained with methanol.…”
Section: Analysis Of the Model For Chestnut Peel Extractssupporting
confidence: 90%
“…The responses of TPC and AC of the chestnut peel extracts are shown in Table 2. The lowest values were obtained with pure ethanol and methanol, which is in agreement with previous studies (Ashraf et al, 2016;Riciputi et al, 2018;DiNardo et al, 2019;Lasano et al, 2019). Results showed that the highest value of TPC (41.92 mg GAE/g DM) was achieved with ethanol, which is in concordance with the result of Stevigny et al (2007), while the highest value of AC (42015.95 mmol AAE/100 g DM) was obtained with methanol.…”
Section: Analysis Of the Model For Chestnut Peel Extractssupporting
confidence: 90%
“…Total Phenolic Content (TPC) was determined using a modified protocol by Dinardo et al (DiNardo et al, 2019a). A quantity of 1 mL of methanolic plum extract was mixed with 7.5 mL double-distilled water and 0.5 mL Folin-Ciocalteu reagent.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…A flow rate of 1 mL/min was used with 20 µL of sample injected. Chromatographic peaks were identified based on the retention time of standard compounds of ascorbic acid, neo-chlorogenic acid, and chlorogenic acid (Figure 1) (Brar, 2017) (DiNardo et al, 2019a. Standard solutions for each compound were prepared in methanol and diluted to various concentrations between 2.5 and 100 µg/mL.…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Absorption for each sample was measured at 517 nm after 20 min of mixing the extract and DPPH solution. Free electrons present in DPPH get paired off in the presence of antioxidants resulting in lower absorption due to the extinction of purple color of DPPH solution (DiNardo et al, 2019a). Scavenging activity on DPPH radicals was expressed as the percentage (%) inhibition using the following equation:…”
Section: Dpph Radical Scavenging Activity Of Peach Powdermentioning
confidence: 99%